Transformación lineal inversa de R² → R²
1
T:R² → R² tal que T(x, y) = (3x - 7y , - x + 2y), si el vector en B es (128 , -38)
2
T:R² → R² tal que T(x, y) = ( - 5x - 6y , 6x - y), si el vector en B es (76 , -83)
3
T:R² → R² tal que T(x, y) = (x + 6y , - x - 5y), si el vector en B es (-67 , 54)
4
T:R² → R² tal que T(x, y) = ( - 5x + 5y , - 5x - 3y), si el vector en B es (40 , 128)
5
T:R² → R² tal que T(x, y) = ( - 7x - 4y , 2x - 2y), si el vector en B es (91 , -4)
6
T:R² → R² tal que T(x, y) = ( - 3x - 7y , - 7x + 6y), si el vector en B es (76 , -247)
7
T:R² → R² tal que T(x, y) = ( - 5x - 8y , - 6x + 3y), si el vector en B es (115 , 75)
8
T:R² → R² tal que T(x, y) = (8x - 4y , - 2x + 5y), si el vector en B es (-72 , -14)
9
T:R² → R² tal que T(x, y) = (8x + 6y , - 2x - y), si el vector en B es (-38 , 17)
10
T:R² → R² tal que T(x, y) = ( - 2x - 7y , - 9x - 2y), si el vector en B es (145 , 151)
11
T:R² → R² tal que T(x, y) = (6x + 3y , - 4x - 7y), si el vector en B es (72 , -68)
12
T:R² → R² tal que T(x, y) = (6x - 5y , 2x - 8y), si el vector en B es (5 , 84)
13
T:R² → R² tal que T(x, y) = ( - 5x + 3y , 9x - 5y), si el vector en B es (72 , -130)
14
T:R² → R² tal que T(x, y) = (2x - 8y , 7x - 2y), si el vector en B es (130 , -39)
15
T:R² → R² tal que T(x, y) = ( - 8x + 7y , 3x + y), si el vector en B es (101 , -27)
16
T:R² → R² tal que T(x, y) = ( - 6x + 3y , 6x + 5y), si el vector en B es (90 , -10)
17
T:R² → R² tal que T(x, y) = (4x - 6y , - 2x + 8y), si el vector en B es (-38 , 54)
18
T:R² → R² tal que T(x, y) = (3x - 5y , - 7x + 4y), si el vector en B es (-101 , 159)
19
T:R² → R² tal que T(x, y) = (2x + y , - 2x - 2y), si el vector en B es (-45 , 62)
20
T:R² → R² tal que T(x, y) = ( - 6x - 2y , - 8x - 4y), si el vector en B es (-82 , -116)
21
T:R² → R² tal que T(x, y) = ( - 6x + 5y , 9x - 2y), si el vector en B es (-17 , 20)
22
T:R² → R² tal que T(x, y) = (2x + 2y , x + 9y), si el vector en B es (-42 , -101)
23
T:R² → R² tal que T(x, y) = (2x - 4y , - 5x + y), si el vector en B es (44 , -2)
24
T:R² → R² tal que T(x, y) = ( - 2x - 9y , 6x + 9y), si el vector en B es (-189 , 225)
25
T:R² → R² tal que T(x, y) = ( - 6x + 6y , - x - 4y), si el vector en B es (12 , 82)
26
T:R² → R² tal que T(x, y) = ( - 2x - 4y , 9x + 5y), si el vector en B es (-22 , 73)
27
T:R² → R² tal que T(x, y) = ( - 6x + 5y , - x - 8y), si el vector en B es (61 , -87)
28
T:R² → R² tal que T(x, y) = (4x + 3y , - 3x - 7y), si el vector en B es (109 , -134)
29
T:R² → R² tal que T(x, y) = (8x - 5y , x + 4y), si el vector en B es (-143 , -4)
30
T:R² → R² tal que T(x, y) = ( - 9x + 5y , - 5x + y), si el vector en B es (-111 , -35)
31
T:R² → R² tal que T(x, y) = ( - 3x + 9y , 4x - y), si el vector en B es (-81 , 42)
32
T:R² → R² tal que T(x, y) = ( - 5x - 9y , x - 3y), si el vector en B es (197 , 23)
33
T:R² → R² tal que T(x, y) = (x - 4y , - 3x + y), si el vector en B es (56 , -25)
34
T:R² → R² tal que T(x, y) = (4x + 4y , 4x + y), si el vector en B es (-128 , -77)
35
T:R² → R² tal que T(x, y) = (7x - 4y , - 4x - 3y), si el vector en B es (-81 , 41)
36
T:R² → R² tal que T(x, y) = ( - 4x - 2y , - x + 6y), si el vector en B es (24 , 123)
37
T:R² → R² tal que T(x, y) = (4x - 5y , 9x + 8y), si el vector en B es (116 , 107)
38
T:R² → R² tal que T(x, y) = ( - 6x - 4y , - 2x + 6y), si el vector en B es (108 , 14)
39
T:R² → R² tal que T(x, y) = ( - 6x - 7y , x + 3y), si el vector en B es (125 , -30)
40
T:R² → R² tal que T(x, y) = ( - x - 8y , 6x - 2y), si el vector en B es (52 , -12)
41
T:R² → R² tal que T(x, y) = (3x + 5y , 7x + 8y), si el vector en B es (24 , 78)
42
T:R² → R² tal que T(x, y) = ( - 5x + 5y , 9x + 2y), si el vector en B es (-85 , 131)
43
T:R² → R² tal que T(x, y) = (x - 4y , 8x - 5y), si el vector en B es (-37 , -107)
44
T:R² → R² tal que T(x, y) = (3x + 9y , - 3x + 5y), si el vector en B es (-135 , -117)
45
T:R² → R² tal que T(x, y) = (6x - 3y , 6x + 5y), si el vector en B es (-72 , -56)
46
T:R² → R² tal que T(x, y) = ( - x + 9y , 2x - 5y), si el vector en B es (172 , -110)
47
T:R² → R² tal que T(x, y) = (4x + 6y , 2x + 6y), si el vector en B es (16 , 26)
48
T:R² → R² tal que T(x, y) = (6x - 5y , - 4x - 9y), si el vector en B es (89 , -47)
49
T:R² → R² tal que T(x, y) = ( - 7x + 2y , - 8x + y), si el vector en B es (76 , 110)
50
T:R² → R² tal que T(x, y) = (5x + 4y , 4x + 4y), si el vector en B es (130 , 112)
51
T:R² → R² tal que T(x, y) = ( - 8x + 4y , 5x + 3y), si el vector en B es (20 , -62)
52
T:R² → R² tal que T(x, y) = ( - 7x + 2y , - 3x + 2y), si el vector en B es (12 , -4)
53
T:R² → R² tal que T(x, y) = (2x + y , x + 3y), si el vector en B es (-30 , 0)
54
T:R² → R² tal que T(x, y) = (9x + 2y , - x + 8y), si el vector en B es (-56 , -150)
55
T:R² → R² tal que T(x, y) = (3x - 4y , - x - 9y), si el vector en B es (50 , 4)
56
T:R² → R² tal que T(x, y) = (3x + 7y , - 2x - 2y), si el vector en B es (-27 , 2)
|